In vitro Regeneration of the Medicinal Herb of Nilgiri shola, Acmella calva L. from Leaf Derived Callus - Senthilkumar, P.; Paulsamy, S.; Vijayakumar, K. K.; Kalimuthu, K. (Plant Tissue Culture and Biotechnology, 2009)
Callus culture was initiated from leaf discs on MS supplemented with BAP, NAA and Kn. The highest frequency (95%) of organogenic callus induction was observed in MS containing BAP at 3.0 mg/l and NAA at 0.3 mg/l. Development of adventitious shoots occurred when the calli were subcultured on MS supplemented with BAP alone at the rate of 3.0 mg/l (80%) and BAP with NAA at the rate of 3.0 and 0.3 mg/l, respectively (95%) and BAP with Kn at the rate of 3.0 and 0.3 mg/l, respectively (70%). The root initiation and the rate of growth were higher in the basal medium containing BAP at 3.0 and 2.5 mg/l. The plantlets were establish successfully in the hardening medium composed by coir pith and soil (1 : 1). Key words: Acmella calva, Leaf derived callus, Nilgiris, India Â Â Plant Tissue Cult. & Biotech. 17(2): 109-114, 2007 Â DOI: 10.3329/ptcb.v17i2.2566